Design of K-Band Power Amplifier with 180-Degree Phase- Shift Function Using Low-Power CMOS Process - Seongjin Jang; Jaeyong Lee; Jeong-Woo Lee; Changkun Park (Applied Sciences, 2023)
In this study, a K-band complementary metal oxide semiconductor (CMOS) power amplifier was designed using a low-power (LP) process to improve the integration of the beamforming system. In order to reduce the overall system size, a 180° phase-shift function was mounted. It was designed in a four-stage structure to secure sufficient gain. In addition, we propose a way to secure wideband characteristics by utilizing the gains of each of the four stages. The power amplifier was designed with a 40-nm LP CMOS process to verify the feasibility of the proposed technique. The measured P1dB for 0° and 180° phase-shift modes were 15.25 dBm and 14.30 dBm, respectively, at the operating frequency of 25.0 GHz. The measured phase difference between the two modes was 217° at the 25.0 GHz.